Cost effectiveness of an intervention to increase uptake of hepatitis C virus testing and treatment (HepCATT): cluster randomised controlled trial in primary care. (26th February 2020) - Roberts, Kirsty; Macleod, John; Metcalfe, Chris; Hollingworth, Will; Williams, Jack; Muir, Peter; Vickerman, Peter; Clement, Clare; Gordon, Fiona; Irving, Will; Waldron, Cherry-Ann; North, Paul; et al.
Abstract: Objective: To evaluate the effectiveness and cost effectiveness of a complex intervention in primary care that aims to increase uptake of hepatitis C virus (HCV) case finding and treatment. Design: Pragmatic, two armed, practice level, cluster randomised controlled trial and economic evaluation. Setting and participants: 45 general practices in South West England (22 randomised to intervention and 23 to control arm). Outcome data were collected from all intervention practices and 21/23 control practices. Total number of flagged patients was 24 473 (about 5% of practice list). Intervention: Electronic algorithm and flag on practice systems identifying patients with HCV risk markers (such as history of opioid dependence or HCV tests with no evidence of referral to hepatology), staff educational training in HCV, and practice posters/leaflets to increase patients' awareness. Flagged patients were invited by letter for an HCV test (with one follow-up) and had on-screen pop-ups to encourage opportunistic testing. The intervention lasted one year, with practices recruited April to December 2016. Main outcome measures: Primary outcome: uptake of HCV testing. Secondary outcomes: number of positive HCV tests and yield (proportion HCV positive); HCV treatment assessment at hepatology; cost effectiveness. Results: Baseline HCV testing of flagged patients (six months before study start) was 608/13 097 (4.6%) in intervention practices and 380/11 376 (3.3%) in control practices. During the study 2071 (16%) of flagged patients in the intervention practices and 1163 (10%) in control practices were tested for HCV: overall intervention effect as an adjusted rate ratio of 1.59 (95% confidence interval 1.21 to 2.08; P<0.001). HCV antibodies were detected in 129 patients from intervention practices and 51 patients from control practices (adjusted rate ratio 2.24, 1.47 to 3.42) with weak evidence of an increase in yield (6.2% v 4.4%; adjusted risk ratio 1.40, 0.99 to 1.95). Referral and assessment increased in intervention practices compared with control practices (adjusted rate ratio 5.78, 1.6 to 21.6) with a risk difference of 1.3 per 1000 and a "number needed to help" of one extra HCV diagnosis, referral, and assessment per 792 (95% confidence interval 558 to 1883) patients flagged. The average cost of HCV case finding was £4.03 (95% confidence interval £2.27 to £5.80) per at risk patient and £3165 per additional patient assessed at hepatology. The incremental cost effectiveness ratio was £6212 per quality adjusted life year (QALY), with 92.5% probability of being below £20 000 per QALY. Conclusion: HepCATT had a modest impact but is a low cost intervention that merits optimisation and implementation as part of an NHS strategy to increase HCV testing and treatment. Trial registration: ISRCTN61788850.